The process of decision making in mipymes hoteleras in Boyaca, Colombia - Moya-Espinosa, Pedro Ignacio; Cortés-Rodríguez, Nubia Consuelo; Martínez-Cárdenas, Ana Graciela (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The article looks for the identification process of Decision Making, DM, in hotel companies affiliated to the Hotel and Tourism Association of Colombia, Cotelco, Boyacá Chapter. The characteristics, process and tools used in the DM were established, highlighting that it is a process in which, among several alternatives, one is chosen that can guide the courses of action and solve a current or potential problem. The research is exploratory and descriptive and it started by doing a literature review, then, a structured survey was applied to 54 of 59 managers as the target population. The results indicate that the companies studied correspond in a 70.9% to microenterprises, where the managers develop a structured process in the DM, with a tendency to apply some actions to the use of management tools in quality management and customer service.